Different Trajectories of Apathy and Depression Among Subjective Cognitive Impairment Individuals with or without Conversion to Dementia: Results from the Memento Cohort in France. - Bogdan, Anamaria; Fabre, Roxane; Desmidt, Thomas; Golebiowski, Jérôme; Topin, Jérémie; Bethus, Ingrid; Hanon, Olivier; Boutoleau-Bretonnière, Claire; Wagemann, Nathalie; Annweiler, Cedric; Ousset, Pierre-Jean; Godefroy, Olivier; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Apathy and depression are two early behavioral symptoms in Alzheimer's disease (AD) and related disorders that often occur prior to the onset of cognitive decline and memory disturbances. Both have been associated with an increased risk of conversion to dementia, with a distinct neuropathology. OBJECTIVE: The assessment of the trajectories of apathy and depression and their independent impact on dementia conversion. METHODS: Apathy and Depression were measured using the Neuropsychiatric Inventory for caregiver (NPI) and clinician (NPI-C), among the nondemented individuals reporting subjective cognitive decline (SCD) at baseline. They were followed up over a 60-month period. Some converted to dementia, according to the methodology carried out by the French Memento Cohort. RESULTS: Among individuals with SCD (n = 2,323), the levels of apathy and depression were low and did not evolve significantly over the 60-month period, despite a trend in apathy increasing as of month 24. Regarding SCD individuals who converted to dementia within the 60-month period (n = 27), the prevalence of depression remained globally steady, while the levels of apathy increased over time. CONCLUSION: Apathy and depression have different trajectories among individuals with SCD and apathy alone is more likely-compared to depression-to be associated with conversion to dementia.

Evolution of the Antidepressant Prescribing in Alzheimer's Disease and Related Disorders Between 2010 and 2014: Results from the French National Database on Alzheimer's Disease (BNA). - David, Renaud; Manera, Valeria; Fabre, Roxane; Pradier, Christian; Robert, Philippe; Tifratene, Karim (J Alzheimers Dis, 2016)
BACKGROUND: Safety warnings from health authorities are currently intended to limit the use of psychotropic agents in dementia-related conditions. Evidence concerning the use of antidepressants in dementia is, however, scarce and contradictory. OBJECTIVE: To evaluate antidepressant use among individuals with Alzheimer's disease (AD) and related disorders in the French population between 2010 and 2014. METHOD: Antidepressant prescriptions in individuals with AD, mixed dementia (MD), and vascular dementia (VaD) in the French National Alzheimer Database between 2010 and 2014 were analyzed (N = 199,544). RESULTS: Multivariate analysis showed an annual significant increase (p < 0.001) in the prescription rate of antidepressants from 26% (2010) to 31% (2014), and identified female gender, younger age, higher education, living in long-term facilities, more severe cognitive decline, and presence of vascular signs (VaD and MD) as associated factors for antidepressant prescribing. CONCLUSION: The annual increase of antidepressant prescribing among individuals with AD, MD, and VaD in French specialized settings may be partially related to the lack of current valuable medications for dementia-related behavioral symptoms.